2022
DOI: 10.22159/ijpps.2022v14i4.43181
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking Study on Phytoconstituents of Traditional Ayurvedic Drug Tulsi (Ocimum Sanctum Linn.) Against Covid-19 Mpro Enzyme: An in Silico Study

Abstract: Objective: The aim of the present study was to assess bioactive compounds found in Tulsi as potential COVID-19 Mpr °inhibitor using molecular docking and to provide scientific justification in term of its active ingredient to target protein for prevention and symptomatic treatment of COVID-19. Methods: COVID-19 Mpr °was docked with eight phytochemicals of Ocimum sanctum Linn. Using Autodock 4.2. Determination of active site and visualization of molecular interactions between ligands and target enzyme was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Since the first approval of the first Jakinib that is ruxolitinib, for myeloproliferative disorders, a total of 12 Jakinibs have been approved for an array of autoimmune and inflammatory conditions. Coronavirus-2019 (COVID-19) pandemic is caused by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) and is characterized by a respiratory illness, multiple organ failure, pneumonia, acute respiratory distress syndrome (ARDS), and finally, death (Agrawal et al, 2020;Jain et al, 2022). In addition to these symptoms, patients with this condition exhibit several systemic manifestations, such as lymphopenia, abnormalities of ferritin levels, prothrombin time, platelet count, acute partial thromboplastin time, and blood clotting anomalies (Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Since the first approval of the first Jakinib that is ruxolitinib, for myeloproliferative disorders, a total of 12 Jakinibs have been approved for an array of autoimmune and inflammatory conditions. Coronavirus-2019 (COVID-19) pandemic is caused by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) and is characterized by a respiratory illness, multiple organ failure, pneumonia, acute respiratory distress syndrome (ARDS), and finally, death (Agrawal et al, 2020;Jain et al, 2022). In addition to these symptoms, patients with this condition exhibit several systemic manifestations, such as lymphopenia, abnormalities of ferritin levels, prothrombin time, platelet count, acute partial thromboplastin time, and blood clotting anomalies (Zhang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Various computational tools and databases were used to investigate and predict the bioactive compounds, potential gene targets, and pathways involved in the pharmacological network of A. laxiflora on depressive disorder. In addition, Molecular docking techniques were used to validate the potential underlying mechanisms ( Jain et al, 2022a ; Abunuwar et al, 2023 ; Najmi et al, 2023 ). An outline of the methodological approach in our current study is demonstrated in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Consuming Tulsi tea can improve the immune system and fight all types of cold, and respiratory inflammations which has become a common practice in South Asia (Kumar et al, 2013). Jain et al (2022) used a molecular docking system to assess the potential of Tulsi as an adjunct therapy for the prevention and symptomatic treatment of COVID-19. Authors reported that among vicenin, caryophyllene, cirsimaritin, isothymusin, and isothymonin, vicenin exhibited better binding energy, that is, −7.02 kcal/mol to COVID-19 main protease through some responsible interactions to inhibit the replication of SARS-CoV-2 in the human body.…”
Section: Tulsimentioning
confidence: 99%